A Classification of the Yamato-75 Chondrites Based on Chemical Compositions of Olivines and Pyroxenes - Matsumoto, Yukio; Hayashi, Masao; Miyamoto, Masamichi; Takeda, Hiroshi; Yanai, Keizo (1979)
P(論文) Electron microprobe studies have been made of olivines and pyroxenes in fifteen Yamato chondrites which were collected from the Yamato Mountains area, East Antarctica by the 16th Japanese Antarctic Research Expedition (1974-1976). Of these meteorites, thirteen chondrites are described for the first time, and two other chondrites (Yamato-75028 and -75102) were already reported by YANAI et al. (Mem. Natl Inst. Polar Res., Spec. Issue, 8,110,1978). The very small fragments used for the analyses were so chipped from the meteorites that contamination to the original materials is minimal. On the basis of histogram of iron contents of olivines and orthopyroxenes, the following predominance have been identified : viz., 1 unequilibrated chondrite; 2 H type and 3 L type moderately equilibrated ordinary chondrites; and 4 H type and 5 L type equilibrated chondrites. The absence of the E type chondrite and the predominance of the H and L type chondrites are notable features but may not be significant at this stage of identification. departmental bulletin paper